2015
DOI: 10.1111/sms.12546
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence and other pelvic floor dysfunctions in female athletes in Brazil: A cross‐sectional study

Abstract: The pelvic floor (PF) provides support to all pelvic organs, as well as appropriately closure/opening mechanism of the urethra, vagina, and anus. Therefore, it is likely that female athletes involved in high-impact and in strong-effort activities are at risk for the occurrence of urinary incontinence (UI). This study aimed to investigate the occurrence of UI and other PF dysfunctions (PFD) [anal incontinence (AI), symptoms of constipation, dyspareunia, vaginal laxity, and pelvic organ prolapse] in 67 amateur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
7
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 42 publications
5
65
7
18
Order By: Relevance
“…Other studies have a wide prevalence range in swimmers, varying from 6%16 to 84.6% 17. Although in aquatic sports the body is partially immersed in water and therefore ground reaction forces have no impact on the pelvic floor, some differences could exist between modalities in terms of abrupt and repetitive increases in IAP due to twisting and other specific sport body movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have a wide prevalence range in swimmers, varying from 6%16 to 84.6% 17. Although in aquatic sports the body is partially immersed in water and therefore ground reaction forces have no impact on the pelvic floor, some differences could exist between modalities in terms of abrupt and repetitive increases in IAP due to twisting and other specific sport body movements.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Bø15 showed that the highest prevalence of UI during sports involved high-impact activities, such as gymnastics and ball games. Regarding the prevalence of UI in different sports, the rates vary between 0% in golf players16 and 88.9% in artistic gymnastics and trampoline athletes 17…”
Section: Introductionmentioning
confidence: 99%
“…18 In another report, athletes exhibited greater odds for urinary incontinence compared to non-athletes (OR=2.90; 95% CI: 1.50–5.61), with ~27% of controls reporting mostly urgency urinary incontinence and ~52% of athletes reporting mostly stress urinary incontinence. 19 Interestingly, self-reported bowel function was better among athletes compared to controls and only controls reported any symptoms of pelvic organ prolapse, yet the authors warn of potential PF damage for women engaged in sporting activity.…”
Section: Literature Updatementioning
confidence: 98%
“…Recentemente tem sido descrito nos estudos a IU em mulheres relacionada ao esporte 10,11,23,24 .A prevalência de IU em atletas está associada com o tipo de esporte, sendo que o acometimento é mais comum em praticantes de esportes de alto impacto 6,1 . É importante ressaltar que trata-se de uma situação que afeta o componente psicológico da atleta, podendo levar ao abandono do esporte e consequente inatividade, tanto da atleta competitiva como da atleta recreacional 14,21,25 .…”
Section: Prevalência De Iuunclassified